2019
DOI: 10.1360/n052018-00159
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of functional amino acids on oxidative stress in pigs

Abstract: Amino acids in the regulation of aging and aging-related diseases Translational Medicine of Aging 3, 70 (2019); Is the kafirin profile capable of modulating the ileal digestibility of amino acids in a soybean meal-sorghum diet fed to pigs?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
0
0
2
Order By: Relevance
“…The forecast peak amplitude of SSN based on SSA in this paper is larger than that based on F 10.7 as the data set and is supported by fewer studies. Han &Yin (2019) andMcIntosh et al (2020) reported similar forecast results, which showed a stronger trend of SSN of SC-25 than in the prior solar cycle. Additionally, there are several forecasting results focused on SSA for SC-25 that are not listed in Table 5.…”
Section: Comparing With Earlier Methodssupporting
confidence: 53%
“…The forecast peak amplitude of SSN based on SSA in this paper is larger than that based on F 10.7 as the data set and is supported by fewer studies. Han &Yin (2019) andMcIntosh et al (2020) reported similar forecast results, which showed a stronger trend of SSN of SC-25 than in the prior solar cycle. Additionally, there are several forecasting results focused on SSA for SC-25 that are not listed in Table 5.…”
Section: Comparing With Earlier Methodssupporting
confidence: 53%
“…例如以稻米为主要成分的日 粮中添加硒后, 肉鸡胸肌肉中的硒含量并没有显著增 加 [21] . 热应激条件下机体氧化应激反应增强 [22,23] 24,25] . 有机硒更容易转运进入肌 肉, 因为硒代蛋氨酸可依赖蛋氨酸转运载体而被主动 吸收, 且硒代蛋氨酸可代替蛋氨酸参与蛋白质合成, 从而储存在动物肌肉中 [21] .…”
Section: 与亚硒酸钠相比 酵母硒可显著提高猪肉和中国地方unclassified
“…"理想氨基酸""理想蛋白质"和氨基酸平衡的研究进行 把这一类氨基酸定义为"功能性氨基酸" [26~28] , 猪功能 性氨基酸营养研究在近十年取得了非常大的进展, 其 中包括在氧化应激、免疫应答、肠道发育、微生物组 成 和 功 能 以 及 机 体 营 养 代 谢 过 程 中 的 调 控 作 用 [26,27,29,30] . 与此同时, 饲料配方过程中除了赖氨酸、 [32] .…”
unclassified